2023
DOI: 10.1093/europace/euac258
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic visualization of coronary arteries: a case series to elicit safety, feasibility, and diagnostic value in complex ablation procedures

Abstract: Aims The goal of this case series was to evaluate the feasibility, safety, and advantages of a wire-based approach for the live visualization of coronary arteries (CAs) in an electroanatomic mapping (EAM) system and to assess its diagnostic information. Methods and results For this single-centre case series, we included procedures in which close proximity of a possible ablation site to any epicardial vessel was suspected. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Kataoka et al 15 assessed the bipolar electrograms within the LCX and treated a challenging scar-related VT case by an ethanol infusion. Recently, Fries et al 7 reported the feasibility of visualizing the coronary arteries on the electroanatomical map by wire mapping. To the best of our knowledge, this is the first report to assess the abnormal bipolar electrograms from coronary arteries and to create a high-density transcoronary map.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kataoka et al 15 assessed the bipolar electrograms within the LCX and treated a challenging scar-related VT case by an ethanol infusion. Recently, Fries et al 7 reported the feasibility of visualizing the coronary arteries on the electroanatomical map by wire mapping. To the best of our knowledge, this is the first report to assess the abnormal bipolar electrograms from coronary arteries and to create a high-density transcoronary map.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 The development of electroanatomical maps strongly supports assessing the scar-related substrate and VT circuit. 5 , 6 Fries et al 7 successfully delineated coronary arteries with a wire used for an electroanatomical map. In this study, we evaluated the ventricular substrate and VT circuit from the coronary arteries in addition to the left ventricular (LV) endocardium and venous system using an over-the-wire microelectrode catheter.…”
Section: Introductionmentioning
confidence: 99%